Assessment of Chemical Risk Literacy among Secondary School Students in the Context of Industrial Disaster Mitigation - Anindyajati, Albertus Digwijaya; Maarif, Syamsul; Bangun, Ernalem (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2025)
This study examines the level of chemical risk literacy among secondary school students residing in industrial areas prone to chemical disasters. The research focuses on SMAN 2 Krakatau Steel Cilegon, located near a chemical industrial zone. The aim is to assess students’ understanding of hazardous chemicals, their preparedness for chemical incidents, and the role of teachers, the Regional Disaster Management Agency (BPBD), and industry in supporting such literacy. Employing a descriptive qualitative approach, data were gathered through interviews, observations, and document analysis. The findings reveal that students’ literacy remains largely theoretical and disconnected from actual environmental risks. Contributing factors include a lack of contextual curriculum, insufficient teacher training, and the absence of joint simulations with BPBD and local industry. This study concludes that a risk-based education approach and contextual assessment are essential to enhance school preparedness for chemical disasters.